Measurement of the Quality Factor for the Micro Electromechanical System Cantilever Devices by Using Non-Destructive Test Methodology - Ozdemir, Savas (University of Waterloo, 2014)
Development of the reliability and the performance of Micro Electro Mechanical System (MEMS) devices are the most challenging tasks of scientists and engineers. At the same time, there is a need for advance and more complex testing methods determining functional, performance of the MEMS device and to predict device performance from wafer test. Recent developments in the technologies are giving opportunities to the researchers in developing suitable non-destructive Test (NDT) methodologies for testing and evaluation of the MEMS [1]. Among several challenges regarding the commercialization of MEMS technologies, the focus of the current thesis will be to prove reliability of the MEMS devices, to determine performance criteria such as Q-factor. With regards to reliability and Q-factor; stiction, noise and squeeze film damping are the important occurrences thereby, this report provides very brief general information about these subjects that is to say detailed examination of these are not the main purpose of this thesis. MEMS technology is a promising platform for next generation sensors and actuators. Despite a substantial amount of research in the field, there are still many challenges regarding the management of energy dissipation in MEMS which limits their performance and reliability. Especially integrated MEMS devices require NDT methods to dynamically test the MEMS structures. In the current thesis, MEMS cantilever beams have been used as representative samples. Moreover, information about their performance criteria is provided, and challenges for the next generation of MEMS devices are discussed. A simple method of logarithmic decrement was applied to calculate the Q- factor of several cantilever beams. Furthermore, the project attempts to show how the contacted cantilever affects the Q-factor of the MEMS devices. Representative samples have been tested under normal air pressure and vacuum in order to eliminate the effect of squeeze film damping factor. The beam was then stuck as both line and area contact to substrate due to surface tension caused by increasing the high electrostatic forces. This way, the stuck beams were stressed because of the deformation caused by the stiction. The maximum contacted area obtained in this study was 30-40% of length. The Q-factor of the contacted and free standing MEMS cantilever switches was then experimentally evaluated. The project demonstrated an experimental set-up that utilizes a scanning laser Doppler vibrometer (LDV) with a novel calculation methodology to measure the Q-factor. Brief information was provided about the MEMS marketing and application to determine the developmental trend of the MEMS devices. Relatedly, potential future research areas related to the MEMS devices was discussed. Deeper insights on enabling technologies, materials and packaging are beyond the scope of the current thesis. The goal of this thesis is to demonstrate the measurement of Q-factor of the cantilever MEMS devices using NDT methodology and to apply calculation methods which is developed based on the best fitted envelope function methodology. The novelty of this project is to experimentally demonstrate a dramatic increase in the Q-factor quadruples as contact evolves from line to area contact.
Keywords: Quality Factor; MEMS Actuators; MEMS cantilever; Damping; Non-Destructive Test methodology; Mechanical Engineering